Risk Factors for Anemia In Pregnant Women: Literature Review - Indraswari, Nys Faizah Nurfitria; Muklis, Ahmad (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to analyze the factors influencing the occurrence of anemia in pregnant women. Anemia in pregnancy is a significant health concern, affecting maternal and fetal outcomes. Identifying and understanding these risk factors is crucial for prevention and management. Methods: A literature review focused on scientific articles published between 2019 and 2024 with the keywords "anemia" and "pregnancy." A total of 8 articles met the inclusion criteria and were thoroughly analyzed to identify common risk factors. Results: The analysis revealed several risk factors associated with anemia in pregnant women. Key findings include iron supplementation; pregnant women who do not adhere to iron tablet consumption have a higher risk of anemia. Education level, higher education-level women have better knowledge about anemia prevention and reducing their risk. Parity Higher parity is linked to an increased risk of anemia. Nutritional Status Pregnant women with poor nutritional status are more likely to develop anemia. Gestational Age The risk of anemia increases with advancing gestational age. Multiple Pregnancies Women with multiple pregnancies are at a higher risk compared to those with single pregnancies. Antenatal Visits Failure to follow recommended antenatal visit schedules increases the risk of anemia. Socioeconomic Status Lower socioeconomic status is associated with a higher risk of anemia. Conclusion: Anemia in pregnant women can be prevented by improving knowledge about the importance of iron consumption, ensuring adequate nutritional intake, enhancing access to and compliance with antenatal services, and providing special attention to high-risk groups. These interventions are essential for reducing the incidence of anemia and improving maternal and fetal health outcomes.